The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1071/fp11031
|View full text |Cite
|
Sign up to set email alerts
|

Large root systems: are they useful in adapting wheat to dry environments?

Abstract: Abstract. There is little consensus on whether having a large root system is the best strategy in adapting wheat (Triticum aestivum L.) to water-limited environments. We explore the reasons for the lack of consensus and aim to answer the question of whether a large root system is useful in adapting wheat to dry environments. We used unpublished data from glasshouse and field experiments examining the relationship between root system size and their functional implication for water capture. Individual root trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
187
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(216 citation statements)
references
References 53 publications
8
187
0
Order By: Relevance
“…Recent work examining Arabidopsis thaliana showed that shoot and root growth are indeed under the same genetic control (Bouteillé et al 2012; and references therein). These results suggest that any advantages conferred by bigger root systems in terms of additional water extraction might be offset by the presence of a larger shoot consuming the extra water (Palta et al 2011). Two recent modelling studies showed exactly that: faster root growth generally led to faster soil water depletion, which subsequently led to yield penalties in soybean ) and chickpea .…”
Section: Are Root and Shoot Growth Under Common Or Independent Genetimentioning
confidence: 94%
See 2 more Smart Citations
“…Recent work examining Arabidopsis thaliana showed that shoot and root growth are indeed under the same genetic control (Bouteillé et al 2012; and references therein). These results suggest that any advantages conferred by bigger root systems in terms of additional water extraction might be offset by the presence of a larger shoot consuming the extra water (Palta et al 2011). Two recent modelling studies showed exactly that: faster root growth generally led to faster soil water depletion, which subsequently led to yield penalties in soybean ) and chickpea .…”
Section: Are Root and Shoot Growth Under Common Or Independent Genetimentioning
confidence: 94%
“…This raises the question as to whether root and shoot growth are under independent or coordinated genetic controls. Root and shoot growth is indeed closely coordinated (Jackson 1993;Palta et al 2011), and abscisic acid (ABA) likely plays a major role in that regulation (Munns and Cramer 1996). It is, in fact, critical for plants to maintain a hydraulic integrity in the soil-root-xylem-leaf-atmosphere continuum to maintain water fluxes (Kudoyarova et al 2013).…”
Section: Are Root and Shoot Growth Under Common Or Independent Genetimentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing importance of subsoil moisture for crop performance implies an advantage of strongly explorative root systems (Kirkegaard et al 2007;Wasson et al 2012). Particularly spring sown cereals may profit from quick root depth penetration to avoid early drought, making better use of post-winter water resources in deeper soil layers (Palta et al 2011). Sustained growth during periods of early season water deficit furthermore enhances quick canopy coverage, thereby reducing soil evaporation and saving stored soil water for crop transpiration.…”
Section: Plant Resistance To Droughtmentioning
confidence: 99%
“…For wheat, physiological and root research studies evidence the significant contribution of roots to higher drought resistance (e.g. Sanguineti et al 2007;Manschadi et al 2008;Palta et al 2011). Wasson et al (2012) give an overview of selection strategies for root improvement of wheat in Australia.…”
Section: Breeding For Dehydration Avoidancementioning
confidence: 99%